Conservative management of primary non-refluxing megaureter during the first year of life: A longitudinal observational study. Issue 4 (August 2015) - Di Renzo, D.; Persico, A.; Di Nicola, M.; Silvaroli, S.; Martino, G.; Lelli Chiesa, P.
Summary: Introduction: There is a lack of prospective studies that include a selected population of patients with primary non-refluxing megaureter (PM). Thus, a longitudinal observational study was designed to follow from birth a selected population of children with PM; all were antenatally diagnosed. In this paper, the outcomes observed in the first year of life are presented. Objective: The primary aim was to follow the natural history of PM. The secondary aim was to monitor the onset of any potential complications such as urinary tract infections (UTIs), need for hospitalization and need for surgical correction. Study design: All children with antenatally diagnosed PM, born between January 2007 and December 2013, were prospectively followed with observational management: renal ultrasonography and clinical evaluation on a 3-month basis; urinalysis and culture in case of symptoms; and mercaptoacetyltriglycine (MAG3) nuclear scan once older than 1 month. Children presenting at birth with mild urinary tract dilatation were included in Group A; those with moderate-to-severe dilatation were included in Group B. Continuous antibiotic prophylaxis (CAP) was administered to Group B. Results: Forty-seven children (44 males, three females) with 58 PM were included in the study. The participants and their corresponding outcomes are shown in the summary Table. The presence of obstruction at renogram was a significant predictor of UTIs and hospitalization. Discussion: The strengths of this study were its prospective nature and its very consistent population. A limitation was the lack of control groups. The results regarding the negligible incidence of complications in Group A and the residual incidence of febrile UTIs (20%) and hospitalization (17%) in Group B, even with CAP, are in line with previous literature. In contrast, there was a higher risk of UTIs observed in children aged older than 6 months. Conclusions: Resolution or improvement is expected in all cases of PM with mild postnatal dilatation, and close to 60% of those with moderate or severe dilatation. Surgery is rarely performed on children younger than 1 year of age. It is safe to observe children with mild urinary tract dilatation without CAP, because the incidence of UTIs is negligible. In those presenting with moderate or severe urinary tract dilatation, despite CAP, a residual incidence of UTIs is seen, and symptomatic patients often require hospitalization. However, UTIs are well tolerated and do not seem to modify outcome. Cases showing obstruction on the MAG3 scan seem to be at higher risk of UTIs and hospitalization. Table Outcomes and events of interest during the first year of life, in the overall population and in the two groups. Group Participants n Primary non-refluxing megaureter n Outcome at 1 year of age Events of interest Resolved n (%) Improved n (%) Stable n (%) Worsened n (%) Afebrile UTIs (%) Febrile UTIs (%) Hospitalization (%) Surgery (%) A + B 47 58 11 (19.0) 30 (51.7) 14 (24.1) 3 (5.2) 3 (6.4) 7 (14.9) 6 (12.8) 2 (4.2) A 13 17 6 (35.3) 11 (64.7) – – 2 (15.4) – – – B 34 41 5 (12.2) 19 (46.3) 14 (34) 3 (7.3) 1 (2.9) 7 (20.6) 6 (17.6) 2 (5.9)